2022
DOI: 10.1039/d2fo01737g
|View full text |Cite
|
Sign up to set email alerts
|

Evening primrose seed extract rich in polyphenols modulates the invasiveness of colon cancer cells by regulating the TYMS expression

Abstract: Natural polyphenols are plant metabolites exhibiting a broad range of biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 61 publications
(118 reference statements)
1
10
0
Order By: Relevance
“…The CACRC mouse model was established with AOM injection, followed by three cycles of proinflammatory DSS oral administration. In this model, carcinogenesis and tumor development in the distal colon were reported previously [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The CACRC mouse model was established with AOM injection, followed by three cycles of proinflammatory DSS oral administration. In this model, carcinogenesis and tumor development in the distal colon were reported previously [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 97%
“…Colitis-associated colorectal cancer was induced by a single intraperitoneal administration of azoxymethane (AOM) at the dose of 10 mg/kg as described earlier [ 19 , 20 ]. One week later, the autoclaved drinking water was replaced by a 1.5% (w/v) dextran sodium sulfate (DSS) solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are an important group of plant metabolites as their consumption reduces the risk of cancer development [6]. The beneficial antitumor effect of these phytochemicals, both as individual compounds and their combinations, is reflected in the elevation of cancer cell death via the stimulation of apoptotic signaling and the inhibition of proliferating signals [7][8][9]. A modulatory effect on the EMT process is also attributed to their role [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A modulatory effect on the EMT process is also attributed to their role [10,11]. Evening primrose extracts (EPE), rich in polyphenols, have been isolated from postindustrial defatted Oenothera paradoxa seeds and revealed potential anti-cancer properties [9,[12][13][14]. It is known that EPE constituents might inhibit the metastatic abilities of cancer cells by downregulating metalloproteinase expression and secretion [15,16].…”
Section: Introductionmentioning
confidence: 99%